1970
DOI: 10.3758/bf03210211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stimulus duration on perceptual onset and offset latencies

Abstract: The effects of stimulus duration on perceptual onset and offset latency were compared in vision and audition. It was found that perceptual onset latency was independent of stimulus duration but that the perceptual offset latency was longer for brief stimuli than for stimuli that exceeded a critical duration. For stimuli longer than the critical duration, the perceptual onset and offset latencies were equal: The same temporal relationships were found in both modalities. The results indicate that for any specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
3

Year Published

1973
1973
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 10 publications
(6 reference statements)
7
109
3
Order By: Relevance
“…For example, Sperling (1960) found that partial reports of the identity of letters embedded in multiletter displays reduced to an asymptotic limit as the duration between array offset and the onset of an indicator to the to-be-reported letter row was increased to around 300 ms. A similar duration has also been estimated by Collins (1967, 1968), who found that identification of nonsense syllables formed by the superposition of one random-dot image upon another decreased with increasing ISI between the two images, reaching asymptote within the range of 100 to 300 ms. Further examinations of the relationship between stimulus duration and persistence have produced evidence that persistence is the inverse of stimulus duration up to a maximum overall duration of 300 ms or less. This inverse duration effect was first demonstrated by Efron (1970aEfron ( , 1970bEfron ( , 1970c, who proposed that a fixed perceptual duration of 240 ms was composed of a minimum perceptual onset latency of 130 ms plus persistence, which was fixed at 110 ms for stimuli with a duration of 130 ms or less and inversely related to stimulus durations greater than 130 ms. Subsequently, Coltheart (1980) extended the duration of persistence to be an inverse function of stimulus duration of up to 300 ms. Coltheart (1980) defined persistence in terms of a visual memory that decays asymptotically, is characteristically visible, and therefore is central or late cortical in origin.…”
Section: Durationmentioning
confidence: 99%
“…For example, Sperling (1960) found that partial reports of the identity of letters embedded in multiletter displays reduced to an asymptotic limit as the duration between array offset and the onset of an indicator to the to-be-reported letter row was increased to around 300 ms. A similar duration has also been estimated by Collins (1967, 1968), who found that identification of nonsense syllables formed by the superposition of one random-dot image upon another decreased with increasing ISI between the two images, reaching asymptote within the range of 100 to 300 ms. Further examinations of the relationship between stimulus duration and persistence have produced evidence that persistence is the inverse of stimulus duration up to a maximum overall duration of 300 ms or less. This inverse duration effect was first demonstrated by Efron (1970aEfron ( , 1970bEfron ( , 1970c, who proposed that a fixed perceptual duration of 240 ms was composed of a minimum perceptual onset latency of 130 ms plus persistence, which was fixed at 110 ms for stimuli with a duration of 130 ms or less and inversely related to stimulus durations greater than 130 ms. Subsequently, Coltheart (1980) extended the duration of persistence to be an inverse function of stimulus duration of up to 300 ms. Coltheart (1980) defined persistence in terms of a visual memory that decays asymptotically, is characteristically visible, and therefore is central or late cortical in origin.…”
Section: Durationmentioning
confidence: 99%
“…The absence of error when the middle interval is filled, as in Experiment IV, might be explained by assuming that the onset of the second stimulus terminated the representation of the first stimulus. Efron (1970) has reported that brief stimuli either visual or auditory, produced a delayed perceptual offset. However, the effect holds only for very brief stimuli, of less than approximately 150 msec in duration, and could not be stretched to cover the errors in the range of 400 to 650 msec found in the present study.…”
Section: =100jmentioning
confidence: 99%
“…The studies concerning visible persistence fall into two groups: (a) Studies concerned with the time difference between stimulus termination and perceptual termination (Adelson, 1978;Appelman, 1980;Bertelson & Tisseyre, 1969;Bowen, Pola, & Matin, 1974;Sakitt, 1976aSakitt, , 1976b and (b) studies concerned with the total phenomenal duration of the stimulus that require reliable judgments of both onset and termination, the estimated stimulus duration being the time difference between judged onset and termination (Efron, 1970a(Efron, , 1970b(Efron, , 1970cHaber & Standing, 1969, 1970Sperling, 1967). There are no statements concerning the actual form of the rise and decay curves or of the complete representation of the stimulus as a function of time in the subject's visual system.…”
Section: Visible Persistencementioning
confidence: 99%
“…There is an essentially arbitrary translation of the TBR on the time axis. The duration of persistence properly is indexed from an onset judgment to a termination judgment (Efron, 1970a(Efron, , 1970b(Efron, , 1970cHaber& Standing, 1969, 1970Sperling, 1967). Onset-to-termination indexing cancels any (subject dependent) constant factor that might relate judgments of simultaneity between auditory and visual events.…”
Section: Duration Of Visible Persistencementioning
confidence: 99%